2015
DOI: 10.1038/ismej.2015.215
|View full text |Cite
|
Sign up to set email alerts
|

Selective consumption and metabolic allocation of terrestrial and algal carbon determine allochthony in lake bacteria

Abstract: Here we explore strategies of resource utilization and allocation of algal versus terrestrially derived carbon (C) by lake bacterioplankton. We quantified the consumption of terrestrial and algal dissolved organic carbon, and the subsequent allocation of these pools to bacterial growth and respiration, based on the δ 13 C isotopic signatures of bacterial biomass and respiratory carbon dioxide (CO 2 ). Our results confirm that bacterial communities preferentially remove algal C from the terrestrially dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 59 publications
6
65
1
Order By: Relevance
“…Similar direct observations of preferential utilization of phytoplankton‐derived carbon by bacteria have been found in other aquatic systems (Kritzberg et al ., ; Guillemette et al ., ) with respect to degradation of dissolved organic carbon (DOC) by bacterioplankton in the water column. This pattern of accessibility also holds true for sedimentary organic matter under our experimental conditions, namely that phytoplankton‐derived carbon pools are more accessible to microbes than pools derived from plant material.…”
Section: Discussionmentioning
confidence: 99%
“…Similar direct observations of preferential utilization of phytoplankton‐derived carbon by bacteria have been found in other aquatic systems (Kritzberg et al ., ; Guillemette et al ., ) with respect to degradation of dissolved organic carbon (DOC) by bacterioplankton in the water column. This pattern of accessibility also holds true for sedimentary organic matter under our experimental conditions, namely that phytoplankton‐derived carbon pools are more accessible to microbes than pools derived from plant material.…”
Section: Discussionmentioning
confidence: 99%
“…Our results do not fully support previous reports on a highly efficient assimilation of OM from various monomers with a generally high total contribution to bacterial biomass production (Kirchman, ), but are rather in agreement with the study of Guillemette et al . () reporting that alga‐derived, carbohydrate‐rich C was preferentially allocated for respiration by lake bacteria. Overall, bacterial OM consumption was directly proportional to the standing stock (i.e., quantity) of different OM compounds released by each alga suggesting non‐selective substrate consumption, as reported for marine bacterioplankton assimilating algal exudates (Sarmento et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it is believed that the main role of glycolate in heterotrophic metabolism is as an energy source (Wright and Shah, 1977;Edenborn and Litchfield, 1987). Recently, a study of carbon utilization in temperate lakes showed that a relatively larger portion of phytoplanktonderived carbon was allocated to respiration (and hence energy conservation), while terrestrial carbon was allocated to biosynthesis (Guillemette et al, 2016). Therefore, glycolate may be an important contributor to the maintenance energy of a persisting cell or could facilitate growth by serving as an energy source, fuelling the subsequent assimilation of terrestrial carbon in winter.…”
Section: Verrucomicrobia-phytoplankton Couplingmentioning
confidence: 99%